urgentíssimoooooooooo
Anexos:
![](https://pt-static.z-dn.net/files/db0/61bbf9c16460d0d878c71df81c639541.jpg)
Soluções para a tarefa
Respondido por
1
F(x) = ax + b; F(-1) = -3; F(0) = -1
F(0) = 0x + b = -1 => b = -1
F(-1) = -1a + b = -3 => -a -1 = -3 => -a = -3 +1 => -a = -2 => a = 2
F(x) = 2x -1
F(0) = 0x + b = -1 => b = -1
F(-1) = -1a + b = -3 => -a -1 = -3 => -a = -3 +1 => -a = -2 => a = 2
F(x) = 2x -1
Perguntas interessantes
Ed. Física,
11 meses atrás
Matemática,
11 meses atrás
Física,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás